UCO Bank : strategic renewal - Maheshwari, Sunil Kumar; Bhat, Ramesh (London : Indian Institute of Management, Ahmedabad, 2016)
On 31 July 2014, Mr. Arun Kaul, the Chairman and Managing Director (CMD) of UCO Bank (UCO) glanced over the yearly financial results of the banking industry for the year 2013-14. He was pleased that UCO Bank was ranked at the top among nationalised Public Sector Banks (PSBs) including State Government owned J&K Bank on most of the performance parameters. UCO bank had been, until recently, going through tough times, and this achievement was nothing short of a miracle. Having achieved financial turnaround of the bank, Mr. Kaul reflected on what his next course of action should be. Was the turnaround of the bank complete? Was this performance sustainable? UCO had been rated low on customer service parameters in a recent survey of the banking industry.
Originally published in Kumar Maheshwari, S., & Bhat, R. (2016). UCO bank - Strategic renewal. BP0390. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kaul, Arun; UCO Bank; Banks and banking